Optimization of reliable cyclic cable layouts in offshore wind farms. Issue 2 (1st February 2021) - Klein, Arne; Haugland, Dag
ABSTRACT: A novel approach for optimizing reliable cable layouts in offshore wind farms is presented. While optimization models traditionally are designed to suggest acyclic cable routes, those developed in this work recognize that cyclic layouts reduce the consequences of cable failures. The models under study take into account that cables cannot cross each other, which, particularly in instances with restrictive cable capacity, can make it attractive to let cables follow a joint trajectory, and visit turbines without connecting to them. A two-layered optimization process is developed. The outer layer is associated with an integer programming problem, which is subject to simultaneous generation of rows and columns representing cable paths. In the inner layer, a problem identifying feasible low cost paths is solved, guided by optimal dual variable values in the continuous relaxation of the former problem. Results from experimental applications to existing wind farms show good promise of the method.